Reconsidering gender norms in childcare within Chinese migrant families in Portugal - Li, Yaqun; Rabot, Jean Martin; Costa, Rosalina Pisco (Frontiers in Sociology, 2024)
Historically, Chinese societies have been characterized by patriarchal structures (Confucianism and filial piety) that assign distinct roles to men and women within the family unit. These norms typically dictate that women take on the primary responsibility for childcare and household duties, while men are expected to be the primary breadwinners. As the authors observe the second generation of Chinese immigrants settling in Portugal, the immigrants grapple with the significant challenge of striving to preserve cultural heritage with the adaptation to Western norms. Therefore, there is a growing recognition of the need to reassess these traditional gender norms. Women in these families are increasingly participating in the workforce, challenging the notion that childcare should be solely to their domain. This study focuses on the experiences of Chinese immigrants, including both married couples and single individuals residing in Portugal. Through qualitative research methods such as interviews (involving 25 participants) and observations, the research aims to gain a nuanced understanding of the attitude and engagement toward childcare, and the ways it differs between men and women in these immigrant families. Participants’ responses indicate that men’s anticipation of women dedicating more time to childcare is notably influenced by educational attainment and financial circumstances. Conversely, women generally believe that being exempt from labor is not a viable alternative irrespective of their educational qualifications. The traditional distribution of caregiving duties does not consistently apply to Chinese female immigrants. By exploring the influence of traditional Confucian culture on migrants’ perspectives and challenges in assuming parental responsibilities, this study highlights gender disparities among Chinese immigrants and propose solutions to address this gender conflict on division.